Assessment of the efciency of Mentha pulegium essential oil to suppress contamination of stored fruits by Botrytis cinerea - Aouadi Ghozlene; Kalai Grami Leila; Taibi Faiza; Bouhlal Rym; Elkahoui Salem; Zaagueri Takoua; Jallouli Slim; Chaanbi Manel; Hajlaoui Mohamed Rabeh; Mediouni Ben Jemâa Jouda (Journal of Plant Diseases and Protection- Springer, 2022)
Essential oils are a real ore rich in bioactive compounds characterized by a wide spectrum of various biological activities. In this context, our research focused on the study of the chemical composition of Mentha pulegium and Myrtus communis essential oils growing in Northeast Algeria as well as the exploration of their antifungal activities in vitro and in vivo against Botrytis cinerea responsible for moulding on strawberries. GC–MS analysis indicated that M. pulegium essential oil was an isomenthone chemotype (55.59%) while M. communis essential oil was characterized as a eucalyptol chemotype (36.82%). M. pulegium essential oil expressed the best antifungal activity either with poisonous medium method (MIC=MFC:2.66 µl/ ml) or with volatile activity method (MIC:30 µl) compared to M. communis essential oil, (MIC:5.33 µl/ml, MFC:10.66 µl/ml) which expressed no volatile activity. Both crude oils completely inhibited the germination of B. cinerea spores and resulted in up to 88% morphological changes in conidia. In vivo tests have revealed the efectiveness of M. pulegium essential oil in completely suppressing grey mould from strawberries previously inoculated with conidia of B. cinerea by direct contact or exposure to vapours. M. pulegium essential oil display weak phytotoxicity towards fumigated strawberries at low temperatures (T<16 °C). This low phytotoxicity was confrmed by the preservation of some physical parameters of strawberries stored at 7 °C such as colour and weight loss